Intention to adopt electric transportation services by university students in emerging countries - Diego Marcelo Cordero; Maria Fernanda Villavicencio; Kleber Antonio Luna; Yonimiler Castillo (PLoS ONE, 2026)
This study analyzed the factors influencing university students’ intention to use electric bus services to commute to campuses in developing countries, specifically in Ecuador, Peru, and Colombia. A technology adoption model was proposed that integrates variables from the Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), and Unified Theory of Acceptance and Use of Technology (UTAUT), which helps in understanding, predicting, and explaining the acceptance and use of technologies, thus facilitating the design of strategies to improve adoption in various contexts. Data were collected from 1,158 students across different academic fields, genders, and academic levels in the countries studied. The analysis was conducted using structural equation modeling with the partial least squares technique. The key factors assessed included attitudes toward electric vehicles, perceived risk, consumer characteristics, emotions, hyperbolic discounting, intention to use electric transport, and social influence. The findings provide valuable insights into the determinants of electric transportation service adoption among university students and offer guidance for implementing sustainable transportation solutions in educational institutions in developing countries.